Hubungan Adat Setempat, Pola Asuh, dan Persepsi Orang Tua dengan Umur Menikah Wanita PUS pada Pernikahan Dini di Kecamatan Karangrayung, Kabupaten Grobogan Tahun 2016 - Okvita Sari; Sri Winarni; Dharminto Dharminto (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
In 2016 there were 1020 marriage perfome in Karangrayung subdistric and (44,8%) was early marriage. The purpose of this study was to analyze relationship beetwen perception and foster pattern, local traditional early marriage, couple of child bearing age in Karangrayung Subdistric Grobogan. This research used explanatory research with cross sectional study desing. The population of women of fertile couples married earlier and recorded in KUA Karangrayung sub district in 2016 as many as 457 people. Samples of women of fertile age couples who married early 80 people were selected by simple random sampling. Data analyze with univariate, bivariate with rank-spearmant correlation ad chi-square good test and significant level α=5%. The result show that local traditional was goog (52,5%), persepction (53,8%). There is no local customary relationship (pvalue = 0.444), authoritarian parenting (0.729), democratic parenting (0.623), parenting permissiveness (0.319), parent perceptions (pvalue = .428) with age of married couples married at marriage early in Karangrayung subdistric Grobogan. Parents are advised not to over-rein in children and more often invite children to discuss in terms of education and childhood romance to reduce the occurrence of early marriage.